A primacy code for odor identity. Issue 1 (December 2017) - Wilson, Christopher; Serrano, Gabriela; Koulakov, Alexei; Rinberg, Dmitry
Abstract Humans can identify visual objects independently of view angle and lighting, words independently of volume and pitch, and smells independently of concentration. The computational principles underlying invariant object recognition remain mostly unknown. Here we propose that, in olfaction, a small and relatively stable set comprised of the earliest activated receptors forms a code for concentration-invariant odor identity. One prediction of this "primacy coding" scheme is that decisions based on odor identity can be made solely using early odor-evoked neural activity. Using an optogenetic masking paradigm, we define the sensory integration time necessary for odor identification and demonstrate that animals can use information occurring <100 ms after inhalation onset to identify odors. Using multi-electrode array recordings of odor responses in the olfactory bulb, we find that concentration-invariant units respond earliest and at latencies that are within this behaviorally-defined time window. We propose a computational model demonstrating how such a code can be read by neural circuits of the olfactory system. Odor identity remains stable despite changes in concentration yet the neural mechanisms are relatively unknown. Here the authors test a primacy coding model using an optogenetic masking paradigm in mice to show that a set of earliest activated receptors are sufficient to make decisions about odor identity across concentrations.